231k views
5 votes
Make t the subject when q equals 2-4t over t+3

User Ostin
by
5.6k points

1 Answer

4 votes

Answer:
t = (2-3q)/(q+4)

This is the same as writing t = (2-3q)/(q+4)

The parenthesis are needed so we know to divide all of "2-3q" all over top "q+4".

==================================================

Work Shown:


q = (2-4t)/(t+3)\\\\\\q(t+3) = 2-4t\\\\\\tq+3q = 2-4t\\\\\\tq+4t = 2-3q\\\\\\t(q+4) = 2-3q\\\\\\t = (2-3q)/(q+4)\\\\\\

To avoid a division by zero error, we need to have
q \\e -4

Also notice how
t = -3 isn't possible for similar reasoning (refer to the first equation at the top).

User Tejogol
by
5.8k points